An Evaluation of Oral Colonisation of Candida In Cigarette Smoking and Tobacco Toxicity: The Impact of Smoking and Tobacco Chewing on Oral Candida Colonisation (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The aim of the present study was Smokingand Tobacco chewing is associated with a variety of effects on the saliva, oralcommensal bacteria and fungi, mainly Candida, which causes Oral Candidiasis,the most common opportunistic fungal infection in man. This evaluation is anattempt to address the effect of cigarette smoking and tobacco chewing on thecolonisation of oral candida.